A review of constructivist teaching practices - Roustaee, Roya; Abdul Kadir, Suhaida; Asimiran, Soaib (IDOSI Publications, 2014)
In recent years, constructivist theory has attracted scholars’ attention in education. In contrast to previous theories of learning, constructivist theories engage the learner in learning process more. Since teachers are an important lever in education, they should be in line with new reforms and alter the environment of classroom accordingly. The first step in changing environment of classroom is the practices that teacher implement in the classroom which should be consistent with new changes. The following paper, reviews the purpose of teaching practices, two main theories of it and strategies for classroom practices.